2015
DOI: 10.1186/s12887-015-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and processes of HIV status disclosure to HIV - infected children aged 4 to 17 years receiving HIV care services at Baylor College of Medicine Children’s Foundation Tanzania, Centre of Excellence (COE) in Mbeya: a cross-sectional study

Abstract: BackgroundDisclosure of HIV sero-status to HIV-infected children is associated with reduced risk of death and better adherence to antiretroviral drugs. However, caregivers find it difficult to determine when and how they should disclose the HIV sero-positive status to HIV-infected children. In this study, we assessed the determinants and processes of HIV status disclosure to HIV-infected children aged 4 to 17 years receiving HIV care services at the Baylor College of Medicine Children's Foundation Tanzania, Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 20 publications
4
40
7
Order By: Relevance
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.2% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.2% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.1% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…Other factors that may influence the decision to disclose include: caregivers wanting their child to improve or maintain a certain level of adherence, the caregiver's level of knowledge of HIV disclosure, and the child or adolescent's status on ART [21][22][23].…”
Section: Severalmentioning
confidence: 99%